Multiband Split-Ring Resonator Based Planar Inverted-F Antenna for 5G Applications - Muhammad Kamran Ishfaq; Tharek Abd Rahman; Hassan Tariq Chattha; Masood Ur Rehman (International Journal of Antennas and Propagation, 2017)
5G, the fifth generation of wireless communications, is focusing on multiple frequency bands, such as 6 GHz, 10 GHz, 15 GHz, 28 GHz, and 38 GHz, to achieve high data rates up to 10 Gbps or more. The industry demands multiband antennas to cover these distant frequency bands, which is a task much more challenging. In this paper, we have designed a novel multiband split-ring resonator (SRR) based planar inverted-F antenna (PIFA) for 5G applications. It is composed of a PIFA, an inverted-L parasitic element, a rectangular shaped parasitic element, and a split-ring resonator (SRR) etched on the top plate of the PIFA. The basic PIFA structure resonates at 6 GHz. An addition of a rectangular shaped parasitic element produces a resonance at 15 GHz. The introduction of a split-ring resonator produces a band notch at 8 GHz, and a resonance at 10 GHz, while the insertion of an inverted-L shaped parasitic element further enhances the impedance bandwidth in the 10 GHz band. The frequency bands covered, each with more than 1 GHz impedance bandwidth, are 6 GHz (5–7 GHz), 10 GHz (9–10.8 GHz), and 15 GHz (14-15 GHz), expected for inclusion in next-generation wireless communications, that is, 5G. The design is simulated using Ansys Electromagnetic Suite 17 simulation software package. The simulated and the measured results are compared and analyzed which are generally in good agreement.